KINERJA PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA (APBDES) TAHUN 2020 DESA WERINAMA KECEMATAN WERINAMA KABUPATEN BULA SBT - Musaid, Sri Astuti; Kesaulya, Juliana; Keliwooy , Fahrun (ISAS, 2023)
The purpose of writing is to analyze the level of effectiveness and efficiency of village fund management in Werinama Village, Werinama District, Eastern Part of Bula Seram Regency. the ratio of effectiveness and efficiency based on Minister of Home Affairs Decree No. 690,900-327 in 1996. The results of this research show the average level of village fund management efficiency in Werinama Village, Werinama District, Bula District, East Seram District. of 96.43% which meets the effectiveness criteria, and the average efficiency level of 46.93% is meant in the very efficient category. Keywords: Werinama Village Fund, Werinama District.